New aesthetics of the city – design of cyclists traffic signs - Stanić, Branimir; Vujin, Darko (Transport, 2005)
In a number of towns and cities worldwide development programmes have been initiated to provide designated bike surfaces reserved for the movement of cyclists along city network. There has been an increase in the use of a bicycle as a regular means of personal transport, particularly in recent years when technical solutions and modern materials have allowed more active use of bicycles in big cities. Judging from the perspective of bicycles, Belgrade has undergone several significant changes. In the period preceding the Second World War the number of bicycles in the city (area of which used to be much smaller than today) was considerable, particularly in relation to vehicles. In the following periods, the development of the city has gradually pushed bicycles towards outskirts. Today bicycles are mostly used for recreation purposes. In this process special signalization addressed to cyclists has been mainly neglected. So‐called standard info‐solutions, essentially addressed to drivers, were applied. New aesthetics of the city, as one of possible ideas of the urban space re‐engineering, is based also on the introduction of “Zones 20” 20 mph (30 km/h) zones as well as on more active use of bicycles. In addition, both mentioned measures increase ecological quality of life in the city. A new concept of info‐system addressed to cyclists moving in a street network of a big city (Case Study of Belgrade, 2004) is presented in this paper. First Published Online: 27 Oct 2010